Multiple Environmental Drivers for the Patagonian Forest-Dwelling Beetles: Contrasting Functional and Taxonomic Responses Across Strata and Trophic Guilds - Vergara-Egert, P; Quiroz-Espinoza, M; Fierro-Tapia, C; Alaniz-Baeza, A; Carvajal-Leon, M (Elsevier B.V., 2022)
Forest disturbances modify microhabitats along the different vertical strata, triggering structural and functional changes in forest-dwelling beetle communities. However, the effects of multiple environmental factors can be complex to detect in ecosystems that offer a broad variety of microhabitats for a great variety of beetle species. This is the case in Patagonian temperate forests, where the use of remote sensing provides an opportunity to evaluate the sensitivity of beetle species to environmental changes. Here, we identified the environmental drivers of forest-dwelling beetle communities in the ground and canopy of 34 north Patagonian-forest landscapes. We analyzed the associations of the taxonomic and functional diversity of five trophic guilds with 30 remote-sensing variables of landscape structure, composition, and disturbances; vegetation and soil properties; and climate and physical variables. Hierarchical clustering analysis was used to identify trophic guilds responding similarly to predictors. Segmented regression analysis was used to evaluate functional redundancy from taxonomic-functional richness relationships. A total of 583 species (23,848 individuals) of beetles were recorded for both strata. The effects of environmental variables were heterogeneous across strata and guilds. Canopy beetles were especially sensitive to early successional conditions, and canopy attributes, but also benefited from the canopy openness. Forest specialists of the ground and canopy responded differently to environmental variables. Ground-dwelling beetles were mostly affected by fires, human modifications, edge closeness, high temperatures, and soil properties, responding weakly to canopy properties. Functional redundancy varied weakly along environmental gradients, being more likely in local communities of ground-dwelling beetles mostly composed of species with overlapping functional roles. Contrasting environmental responses between ground and canopy beetles, as well as among beetles of different trophic guilds, should arise from microhabitats that vary across strata and interact differently with response traits. © 2022 Elsevier B.V.